A new black bean with resistance to bean rust: Registration of 'ND Twilight'. Issue 1 (9th December 2020) - Osorno, Juan M.; Vander Wal, Albert J.; Posch, John; Simons, Kristin; Grafton, Kenneth F.; Pasche, Julie S.; Valentini, Giseli; Pastor‐Corrales, Marcial
Abstract: 'ND Twilight' (Reg. no. CV‐332, PI 693268; PVP‐202000258) is a new black bean ( Phaseolus vulgaris L.) cultivar developed by the Dry Edible Bean Breeding Program at North Dakota State University and released by the North Dakota Agricultural Experiment Station. ND Twilight was developed using a modified pedigree method (F1 –F5 ), followed by pure line selection based on agronomic, disease, and quality traits, along with specific DNA markers. With ∼24% of the total dry bean production in the United States, black bean is the second most important market class after pinto. Accounting for ∼35% of the total production, North Dakota is the largest producer of dry bean in the United States. However, both biotic and abiotic stresses are the main factors responsible for seed yield reductions. Between 2014 and 2019, ND Twilight was tested across more than 21 environments in North Dakota, where seed yield was significantly different from 'Zorro' and similar to 'Eclipse' and 'Loreto'. ND Twilight is resistant to the most common race (20‐3) of the bean rust pathogen and Bean common mosaic virus . It also has intermediate resistance to common bacterial blight and to soybean cyst nematode (HG Type 0). ND Twilight has desirable upright architecture (Type IIa). Under North Dakota conditions, ND Twilight shows an average plant height of 49 cm, has a 100‐seed weight of 19.7 g, and matures in ∼99 d. Canning quality was rated as acceptable. Other traits of agronomic and economic importance are within acceptable commercial ranges. Core Ideas: ND Twilight black bean cultivar has good agronomic performance and disease resistance. This new cultivar has both rust and Bean common mosaic virus resistance. It also has intermediate resistance to common bacterial blight and soybean cyst nematode. The plant architecture is upright. Seed shape, size, color, and canning quality are all within acceptable ranges.